Preclinical hematological profile studies of an ayurvedic medicine Krishna Chaturmukha after chronic administration to male Sprague-Dawley rats - Al Azad, M.; Ohidullah, M.; Nuruzzaman Neon, M.; Sikder, M. Mamun; Choudhuri, M. S. K. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Krishna Chaturmukha (KMC) is an ayurvedic formulation predominantly used as a traditional medicine in the rural population to get relief from various neurological disorders. Methods: The acute pharmacological test of KMC recorded no death or any signs of effectivity even at the highest dose of 4000 mg/kg body weight. The effect of chronic administration of KMC on hematological parameters was determined by administrating chronically to the male Sprague-Dawley rats at a dose of 100 mg per kg body weight for 40 days. Results: There was a (10.12 %) decrease in the number of white blood cell count of the male rats, which, although not statistically significant yet it was prominent (p=0.248). Similarly, a negligible (0.12 %) decrease in the red blood cell count was observed, which was not statistically significant at all (p=0.965). Conversely, the platelets count showed a (4.99 %) increase in the experimental animals, while this increase was not significant, yet it was prominent (p=0.296). Furthermore, a (1.89 %) decline was observed in the platelet volume distribution width of the experiment rats, which, although not significant, yet it was noticeable (p=0.076). Conclusions: From this study, it is evident that there is no significant change in the hematological parameters in the body of the treated rats, therefore it is safe to use in usual dose. Further research and analysis with biochemical parameters should be done to reconfirm the safety of this ayurvedic medicine.